ASSESSMENT ON THE ISLAMIC BANKING MARKET SHARE PROJECTION BY BANK INDONESIA AND PROPOSED METHODS - Sukmana, Raditya; Kuswanto, Heri (Journal of Islamic Monetary Economics and Finance, 2015)
Indonesian Islamic banking market share projected by Bank Indonesia is an integral part in developing the industry in the country. By setting a projection which will then be used as a benchmark / target, Islamic banks can make a necessary program to attract new customers which eventually increase its asset. If the increase of the asset is significant,the Islamic bank market share may increase. The problem is that the current projection by Bank Indonesia seems to be off target. It means that the projection is pretty much above the actual value. This paper attempts to utilize two projection methods namely Spline and Auto-ARIMA which we think can provide a better result. This study uses the monthly data covering period since January 2006 until December 2012. The result shows that our projections, especially using Spline method, are closer to the actual value of the Islamic banking industry market share. It means that the gap between the projection and the actual value of market share is lesser than the gap on the Bank Indonesia calculation. Moreover, this study argue that, the projection of the Islamic banking market share made by BI will not be achieved unless with government support. So far, government has not made any policy which deposit some of the national budget in the Islamic bank. This study calculates that if government regularly depositing 1% of total National Government Budget in Islamic banks, the projection of Islamic banking market share made by BI will be acheived. As a conclusion, the role of government is very significant in developing the Islamic banking industry in Indonesia.